Precarious work, harassment, and the erosion of employment standards. Issue 3 (3rd September 2019) - Perry, J. Adam; Berlingieri, Adriana; Mirchandani, Kiran
Abstract : Purpose: The purpose of this paper is to examine experiences of harassment within the context of precarious work, which in Canada is shaped by subnational legislative frameworks. Design/methodology/approach: A narrative inquiry approach to data collection and analysis was adopted. The paper draws from 72 interviews conducted with workers in precarious jobs from various industries in three cities in the Canadian province of Ontario, as well as 52 employment standards officers (ESOs) from 15 local Ministry of Labour offices in every region across the province. Placing workers' stories in counterpoint to those of ESOs brings them into conversations about the law to which they would normally be left out. Findings: The main finding of this paper is that harassment and employment standards (ES) violations are interrelated phenomena experienced as abuses of power and as tactics of control occurring within a context that is shaped by legislative frameworks. Originality/value: This paper demonstrates that for workers in precarious jobs legislative frameworks and labor market practices in Ontario do not provide adequate redress for harassment and ES violations. In so doing, legislative frameworks render invisible the power imbalances within the employment relationship and obscure the interrelatedness of harassment and the wider erosion of workplace norms.